1998
DOI: 10.1029/98gb00741
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial sedimentation and the carbon cycle: Coupling weathering and erosion to carbon burial

Abstract: The terrestrial sediment cycle is not in equilibrium. Agriculture, civil engineering, and mining mobilize vast quantities of soils, unconsolidated sediment, and bedrock, perhaps more than all natural geomorphic processes combined [Hooke, 1994]. The hydraulic architecture of the land has been transformed to serve agriculture, water supplies, land reclamation, navigation, and power generation. Few rivers lack dams and reservoirs; large rivers are confined to their channels by levees; normal floodplains are conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
668
6
13

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 734 publications
(712 citation statements)
references
References 68 publications
25
668
6
13
Order By: Relevance
“…Erosion by wind and water affects roughly 10×10 12 m 2 of land worldwide (Jacinthe and Lal 2001) and moves 1-5 Pg C y -1 , with more than 70% deposited terrestrially (Stallard, 1998). As a result of the erosion effects on decomposition and NPP described above, recent studies have suggested that erosion results in a global terrestrial C sink of 0.25-1 Pg C y -1 (Stallard 1998;Smith et al 2005;Berhe et al 2007;van Oost et al 2007). …”
Section: Reliefmentioning
confidence: 99%
See 2 more Smart Citations
“…Erosion by wind and water affects roughly 10×10 12 m 2 of land worldwide (Jacinthe and Lal 2001) and moves 1-5 Pg C y -1 , with more than 70% deposited terrestrially (Stallard, 1998). As a result of the erosion effects on decomposition and NPP described above, recent studies have suggested that erosion results in a global terrestrial C sink of 0.25-1 Pg C y -1 (Stallard 1998;Smith et al 2005;Berhe et al 2007;van Oost et al 2007). …”
Section: Reliefmentioning
confidence: 99%
“…In terms of total watershed C stock, recent empirical and modeling studies conclude that erosion-and the balance between its effects on productivity and decomposition in eroding and depositional sites-tends to lead to an increase in stock, even if there are local decreases in the eroding sites themselves (Stallard 1998;Smith et al 2005;Berhe et al 2007;Harden et al 1999).…”
Section: Reliefmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some area of the world where lakes occupy 10e20% of the land surface area, such as Wuhan City, China, lake carbon budget is potentially a very important component of the whole area carbon budget. Studies on carbon burial in lake sediments have shown that lakes are disproportionately important carbon sinks (Dean and Gorham, 1998;Einsele et al, 2001;Mulholland and Elwood, 1982;Stallard, 1998), with the sedimentation mass of organic carbon in lakes about half that of oceans, which cover 71% of the earth's surface (Dean and Gorham, 1998). Compared to large lakes, small lakes are proportionally more important for carbon burial (Kortelainen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Dean & Gorham (1998) estimated global C burial by small lakes to be on the order of 70 g C m −2 yr −1 , based on C accumulation rates in three lakes. Stallard (1998) suggested a lower rate of 4.5 g C m −2 yr −1 . The most comprehensive study is that of Kortelainen et al (2004), who took advantage of the Nordic Lake Survey database and used C standing stock determinations from 122 lakes (mean burden 19 kg m −2 ) to estimate that Holocene C burial by all Finnish lakes is 1.8 g C m −2 yr −1 .…”
Section: Introductionmentioning
confidence: 99%